A Novel Virtual Reality-Based Simulator for Maxillofacial Reconstruction Surgery: Development and Validation Study - Jun-Seong Kim; Kun-Woo Kim; Hyo-Joon Kim; Seong-Yong Moon (Applied Sciences)
Maxillofacial reconstruction surgery involves restoring bones or skeletal structures in areas such as the mouth, jaw, and face using bones like the iliac crest and fibula. This surgery requires a high level of difficulty and precision, necessitating extensive practice and accurate 3D model simulations. However, due to limitations in training environments, opportunities for sufficient practice are restricted, and the precision of simulations may be compromised by the limitations of existing tools. To address these challenges, this paper proposes a maxillofacial reconstruction surgery simulator utilizing virtual reality technology. The proposed method allows users to explore a virtual space through a head-mounted display, where they can visualize, navigate, and manipulate bone models (move and rotate) using the joystick and buttons of a controller, as well as perform resection operations. Additionally, to verify the effectiveness of the simulator, performance evaluation is conducted through frame per second and resource usage analysis, usability testing is performed via questionnaires with dental students, and accuracy validation is carried out for the reconstruction models. The results of each evaluation method are analyzed to confirm the utility and potential of the proposed simulator.